(untitled) (Swiss Medical Weekly, 2014)
Relapsing-remitting multiple sclerosis (RRMS) management has dramatically changed over the past decade. New drugs have arrived on the market, allowing for more individualised treatment selection. However, this diversity has increased the complexity of RRMS patient follow-up. In this review, we provide summarised information about treatment efficacy, potential side-effects, follow-up recommendations, vaccinations, and pregnancy safety issues for all currently available disease modifying therapies and those awaiting approval.